Meta-analysis of average estimates of genetic parameters for growth, reproduction and milk production traits in goats - Jembere, T.; Dessie, Tadelle; Rischkowsky, Barbara A.; Kebede, K.; Okeyo Mwai, Ally; Haile, Aynalem (Elsevier, 2017)
A meta-analysis of 84 published reports on goats was conducted to calculate weighted and unweighted average direct heritability (ha2), maternal genetic effect (hm2), common environmental effect (c2), repeatability (R), genetic (rg) and phenotypic (rp) correlations for growth, reproduction and milk production traits. Weighted average ha2, hm2, and c2 for growth traits ranged from 0.03 to 0.45, 0.05 to 0.27, and 0.02 to 0.10, respectively. Weighted average ha2 for reproduction and milk production traits ranged from 0.00 to 0.17 and 0.15 to 0.22, respectively. Weighted R for the growth, reproduction, and milk production traits ranged from 0.06 to 0.56, 0.06 to 0.13, and 0.50 to 0.61, respectively. Weighted averages of rp and rg among growth traits ranged from −0.06 to 0.84 and 0.01 to 0.98, respectively. Weighted average rp among milk production traits ranged from 0.18 to 0.94. In most cases average ha2 and rg had higher observed standard deviations compared to the theoretical standard error. The present finding revealed that weighted average ha2, hm2, c2, R, and rg are more reliable for two reasons: estimates of ha2 for some growth traits were more conservative than values from relatively higher number of records and the absence of significant effects of the tested fixed factors on some parameter estimates. However, studies on genetic parameter estimations are required for growth, reproduction, and milk traits in goats.